Human resource management gaining a competitive advantage - Noe, Raymond A.
Human Resource Management: Gaining A Competitive Advantage by Noe/Hollenbeck/Gerhart/Wright is back with a new and improved 4th edition. In this new economy, effective human resource management is all the more necessary to gain true competitive advantage in the marketplace, as competitors strive to win the war for talent. Four challenges companies face are the global challenge, the challenge of meeting stakeholder needs, the high performance work practices challenge, and the challenge of competing in the new economy. The authors bring these challenges to life by highlighting real-world examples pertaining to these 4 issues and relating it to the concepts within the chapter. This best-selling McGraw-Hill Human Resource Management title provides students with the technical background needed to be a knowledgeable consumer of human resource (HR) products and services, to manage HR effectively, or to be a successful HR professional. While clearly strategic in nature, the text also emphasizes how managers can more effectively acquire, develop, compensate, and manage the internal and external environment that relates to the management of human resources.